Investigating steeply inclined abandoned mines for unlocking the secrets of water level recovery - Yarui Li; Huiqing Lian; Songlin Yang; Wei Liu; Tao Yan; Hung Vo Thanh; Shangxian Yin; Zhenxue Dai (Scientific Reports)
Abstract With the growing emphasis on environmental protection, many coal mines in northern China were closed. However, the cessation of pumping operations in those closed mines has caused a rise in groundwater levels, giving rise to various safety and environmental concerns. Understanding the patterns of water level recovery is vital for effectively managing abandoned mine sites and ensuring the uninterrupted production of adjacent coal mines. While the groundwater hazards in goaf areas have been extensively studied by scholars, there is a notable scarcity of research on water level recovery in closed coal mines. To address this knowledge gap, this study focuses on investigating the water level recovery patterns in abandoned mine sites, using the Zhaogezhuang Mine as a case study. Based on these research findings, we will conduct future studies of the impact of water level recovery on local communities, the ecological environment, and the geological environment.